Analysis of the Use of Antibiotics in Diarrhea Patients Hospitalization in Internal Disease at RSUP Persahabatan - Meila, Okpri; Nurmutiya, Nurmutiya; V, Atika (Jurnal Midpro, 2020)
Diarrhea is defecation with consistency of liquid (diarrhea) 3 times or more in one day (24 hours). Diarrhea is classified as acute diarrhea and chronic diarrhea. Based on data from the World Health Organization (WHO) there are 2 billion cases of diarrhea in adults worldwide every year. Diarrhea caused by bacteria (arising from heat and simtomsistemic), then the appropriate antibiotic drugs are given. Empirical administration of antibiotics can be done, but specific antibiotic therapy is given based on culture and germ resistance. The study design used descriptive method with cross sectional design. Data retrieval is done retrospectively from medical records. The data is analyzed quantitatively by calculating the DDD formula (Defined Daily Dose) and qualitatively by looking at the accuracy of the selection of antibiotic types, doses and length of antibiotic administration. Based on the results of the study in May-August 2018, 90 samples were included in inclusion. The results of quantitative analysis with DDD / 100 patient days were obtained by Ciprofloxacin iv (34.44) with the highest antibiotic DDD value. The results of the qualitative analysis were based on the exact indication (100%), the right dose (97.08%) and the exact duration of administration (46.26%).